The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1007/s11368-010-0215-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of SDBS–Tween 80 mixed surfactants on the distribution of polycyclic aromatic hydrocarbons in soil–water system

Abstract: Purpose Enhancing desorption of hydrophobic organic contaminants from soils is a promising approach for the effective remediation of soils contaminated with organic compounds. The desorption efficiency of chemical reagent, such as surfactant, should be evaluated. In this study, the effect of mixed anionic-nonionic surfactants sodium dodecylbenzene sulfonate (SDBS)-Tween 80 on the distribution of polycyclic aromatic hydrocarbons in soil-water system was evaluated. Materials and methods Batch desorption experime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(22 citation statements)
references
References 30 publications
3
18
0
1
Order By: Relevance
“…2) and the dispersant adsolubilization of the PAHs. Zhang and Zhu (2010) reported that Tween 80 inhibited desorption of PAHs from soil and they attributed it to elevated hydrophobicity of soil.…”
Section: Effects Of Dispersant On Sorption/desorption Isotherms Of Pahsmentioning
confidence: 99%
“…2) and the dispersant adsolubilization of the PAHs. Zhang and Zhu (2010) reported that Tween 80 inhibited desorption of PAHs from soil and they attributed it to elevated hydrophobicity of soil.…”
Section: Effects Of Dispersant On Sorption/desorption Isotherms Of Pahsmentioning
confidence: 99%
“…Indeed, by mixing SDBS and Tween 80, the strong electrostatic self-repulsions of the former and the steric self-repulsions of the latter decrease due to coexistence around the nanoparticle of both species. At the same time, ion-dipole attractions and Van der Waals forces between the hydrophilic groups of both the surfactants also contribute to strengthening the dispersion [42][43][44][45][46]. It is worth noticing that the A ratio for rGO in SDBS and Tween 80 at 0.1 wt%, as evaluated after a longer time centrifugation of 2 h, results still equal to 0.87.…”
Section: Lubricant Preparation and Stability Dispersion Testsmentioning
confidence: 94%
“…Mohamed and Mahfoodh [34] have also studied the water solubility enhancement of naphthalene and pyrene by micellar solution of single (SDS, Tween 80) and mixed SDS-Tween-80 surfactant systems. Some significant work on solubilization behavior of PAHs is being carried out in various laboratories [35][36][37][38][39]. Kabir-ud-din and his group [40] performed the solubilization aspects of pyrene and anthracene by single and mixed gemini-conventional surfactant systems.…”
Section: Introductionmentioning
confidence: 99%